Pengaruh Penggunaan Telepon Genggam terhadap Perkembangan Akhlak Siswa di Madrasah - Erna Leliana; Mutholingah, Siti (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2025)
The development of digital technology, particularly mobile phones, has brought significant changes to society, including the field of education. This study aims to examine the influence of mobile phone usage on the moral development of students at Madrasah Ibtidaiyah Al Hasib Pakis. The research employed a quantitative approach with an associative design. The population consisted of all MI Al Hasib students, with a sample of 65 students determined using random sampling techniques. The data collection instrument was a questionnaire that had been tested for both validity and reliability. Data analysis was carried out using a simple linear regression test with the assistance of SPSS. The reliability coefficient of the instrument for mobile phone usage was 0.638, while for students’ moral development it was 0.764, both constructed using a Likert scale. The results of the regression analysis showed a constant value of 40.534 and a coefficient of -0.242, indicating that mobile phone usage has a negative effect. The significance test showed a Sig. value of 0.044 < 0.05, which means that mobile phone usage has a significant influence on the moral development of students. Therefore, H1 was accepted and H0 was rejected. The coefficient of determination (R Square) was 0.063, indicating that mobile phone usage contributes 6.3% to students’ moral development, while the remaining percentage is influenced by other variables not examined in this study. Based on the interpretation scale of R, this influence is categorized as very low.